SURVEY GEOFISIKA INDUKSI POLARISASI (IP) MANGAN di NAGARI JAMBAK KECAMATAN LUBUK SIKAPING KABUPATEN PASAMAN - Yoszi Mingsi Anaperta; Mulya Gusman (Universitas Negeri Padang, 2016)
In Pasaman especially Nagari Jambak found several chunks of manganese at some point. To ascertain how big the potential of manganese is available, it is necessary to do some research to see subsurface structure of the earth in order to venture further exploitation (mining) is running properly. One method to determine the subsurface structure of the earth is the geoelectric method of induced polarization (IP). This method utilizes the electrical properties of the rock which is capable of storing a voltage during a certain time interval. Based on the data processing field is not found the deposition of manganese under all three tracks. Resistivity low price on this track, is caused by soil water content in the rock and not because of the rock layer is conductive. Based on the results of these measurements, estimated boulder-boulder manganese contained in the surrounding area of research is not formed in situ at the site proficiency level but rather the result of transport from another location that is above the location of the research